Framtida inhemska proteinfodermedel i den ekologiska fjädefäproduktionen - Kalmendal, Robin (2008)
Organic layers and broilers will according to (EEG) no 2092/91 be fed 100 % organic feeds in year 2012, which is expected to present problems associated with the specific protein requirements of poultry. This document aims at describing the feedstuffs that possibly may constitute a part of the solution to these problems. Peas, field beans, naked oats, canola, hempseed and sunflower come out as interesting feedstuffs. Biproducts from the milling and dairy industry together with marine protein supplements may be brought to the fore, provided that the demand for organic products will rise further.